Effect of anti-PMSG on the ovulatorv response and serum hormone levels in surti goats superovttlated with PMSG - PATEL, A V; DESHPANDE, S B; SARVAIYA, N P; DUGWEKAR, Y G (The Indian Journal of Animal Reproduction, 2023)
The morphological changes in ovaries and hormonal changes after superovulation by PMSG ( I 000 I.U.)and its neutralization with Anti-PMSG administered 8-10 hours after the onset of estrus were studied in Surti goats.Anti-PMSG decreased the number ofunovulated follicles from 6.5 in control to 3 .83 in treated animals and increasedthe ovulations from 2.17 in control to 3.83 in treated animals. The estradiol levels decreased after onset of estrusand increased level of progesterone were observed in the treated animals. However. the differences were statisticallynon-significant.
Keywords: PMSG; anti-PMSG; superovulation; ovarian steroids